Peripartum cardiomyopathy - Rare, unknown and life-threatening - Laverde-Sábogál, Carlos Eduardo; Garnica-Rosas, Lina María; Correa-González, Néstor (Colombian Journal of Anesthesiology, 2016)
Objectives: To present a clinical case and to conduct a non-systematic review of the literature on peripartum cardiomyopathy, and to describe its incidence, aetiology and pathophysiology. Material and methods: With the authorization of the Ethics Committee of our institution, we present the case of a patient of mestizo ethnic origin who developed asthenia, adynamia, lower limb asymmetrical pain and functional class deterioration during the post-partum period, and her management in the Intensive Care Unit and final outcome. The search of the literature was conducted in PubMed, Scielo and Bireme. Results: Peripartum cardiomyopathy is associated with significant morbidity and mortality. The clinical course varies between progressive improvement, heart failure, transplant or death. Some national reports were found. Conclusions: Peripartum cardiomyopathy affects a young and healthy population during a period of time ranging between the end of pregnancy and five months postpartum. The aetiology and pathogenesis are unknown, but several hypotheses have been proposed: viral myocarditis, autoimmune and/or abnormal haemodynamic response to the pregnancy, genetic susceptibility, malnutrition, and apoptosis. The prognosis of recovery of left ventricular function (LVEF) depends on early detection within seven days of the onset of symptoms, an initial LVEF greater than 30%, and a left ventricular diastolic diameter (LVDD) smaller than 60 mm. Mortality is associated with parity greater than four, older age and black ethnc background (6.4 times higher than in Caucasians).